Rock Dynamic Fracture Characteristics by Mini-Linear Shaped Charge Jet Penetration: A Case Study. (30th March 2022) - Xu, Zhenyang; Liu, Xin; Mo, Hongyi; Guo, Lianjun; Yang, Jun
Abstract : An insignificant number of studies have focused on employing penetration using mini-linear shaped charge jets for directionally controlled splitting of massive rocks. In this study, we adopt a numerical calculation method to simulate the penetration and formation of the main splitting surface of a concrete specimen, considering a wedge angle of 45° in both processes. The surface on the principal axial plane is found to split first due to linear jet penetration. In the case of single primary-plane splitting, cracks appear at both ends of the long axis of the penetration crack and the splitting surface extends diagonally from the center of the penetration. A transverse crack separates the splitting surface and the radial-fracture surface, and the degree of fracture decreases along the direction of the height of the specimen. Finally, a realistic physical model demonstrating penetration using a mini-linearshaped charge jet is established. It is a rapid and safe blasting technology to handle hazardous massive rocks during emergency rescuing or mining.